Implementation of Differentiated Learning in the Independent Curriculum at SMPN 3 Kecamatan IV Jurai, Pesisir Selatan Regency - Harisnawati Harisnawati; Yanti Sri Wahyuni; Sri Rahayu; Vivi Andriani; Sinta Fidia Sari (Jurnal Mamangan, 2024)
The Independent Curriculum (Kurikulum Merdeka) has been implemented at SMPN 1 Kecamatan IV Jurai, Pesisir Selatan Regency since the 2022/2023 academic year. The school has conducted workshops at the beginning of each semester to socialize the Independent Curriculum and develop teaching materials in the form of teaching modules. Teachers have also created belajar.id accounts and joined subject-specific communities both within the school and in communities across the regency. This study is motivated by several challenges encountered in implementing the Independent Curriculum, particularly in differentiated learning. These challenges include teachers’ difficulties in recognizing and understanding the individual needs of each student, such as their skill levels, interests, learning styles, and learning preferences. Additionally, teachers face challenges in developing diverse teaching materials that meet students’ needs. Therefore, this study aims to analyze the implementation of differentiated learning within the Independent Curriculum at SMPN 3 Kecamatan IV Jurai, Pesisir Selatan Regency. This research employs a qualitative approach with a descriptive method. The informants consist of the principal, curriculum vice-principal, student affairs vice-principal, and eight teachers at SMPN 1 Kecamatan IV Jurai, selected using purposive sampling. The data consist of primary and secondary data collected through interviews and document studies. Data analysis follows the interactive model by Miles and Huberman, which includes data collection, data reduction, data presentation, and conclusion drawing. The results indicate several stages in implementing differentiated learning: 1) understanding students through diagnostic tests, both academic and non-academic; 2) formulating learning objectives; 3) developing differentiated learning strategies; and 4) using ongoing assessment. Three approaches are applied in differentiated learning at SMPN 3 Kecamatan IV Jurai, Pesisir Selatan Regency: content differentiation, process differentiation, and product differentiation.